The Effect of Health Facilities and Waiting Time on Outpatient Satisfaction at Bondo Kodi Public Health Center - Ronaldus Asto Dadut (Health Notions, 2020)
This study aims to analyze the influence of service quality, health facilities, and waiting times partially and simultaneously on outpatient satisfaction partially in the Bondo Kodi Public Health Center. This research was based on the results of preliminary observations that show the level of satisfaction of patien was still relatively low on health services provided. This research was explanatory research with quantitative approaches. This study was conducted in the Bondo Kodi Public Health Center. The population used in this study were all patients who had utilized health services. The sampling technique was done by purposive sampling, namely by using criteria. Data collection used questionnaires. Then the data analysis used was multiple linear regression analysis. The results of this study showed that service quality (0.000), health facilities (0.030), and waiting time (0.031) influence patient satisfaction at the Bondo Kodi Public Health Center. The results explained that improvements in the quality of services and health facilities will improve patient satisfaction, but at an increasingly shorter waiting time it will also increase patient satisfaction in Bondo Kodi Health Center. Keywords: service quality; health facilities; waiting time; satisfaction